Identification of Synthetic Dyes Red Syrup Beverage Products at Local City of Makasar with Thin Layer Chromatography Methode and Visible Spectrophotometry - Ajeng Kurniati Roddu; Suherman Baharuddin; Holinda Anggrainy (Journal of World Future Medicine, Health and Nursing, 2024)
Colorants are known to be food additives as ordinary colors and artificial colors, which when added or applied to food can give or further develop variety. As a shade of food or water, including carotene, rivoflavin, cobalamin, caramel, chlorophyll, myoglobin, hemoglobin, anthocyanins, flavonoids, quinones, and xanthones. To distinguish the red color produced in Makassar's homemade sweetened water by using the techniques of minimum base chromatography and visible light spectrophutometry and to determine the suitability of the color used with the Indonesian Population Guidelines Order 033 Period 2012 concerning food additives. Techniques: This kind of exploration uses a logical graphic strategy (perception of the research center) which means to get a picture of the utilization of a food additive, specifically the processed red color as a shade in water private-made sweeteners circulating in the Makassar section market. A sample of privately made sweeteners from the Makassar section tested positive for manufactured red color Carmoisine, which is an engineered shading agent allowed in food. The level of Carmoisine in the sweetener testing was 36.31 mg. kg, this indicates that the color level of Carmoisine meets the requirements specified in the Population and Safety Guidelines of the Republic of Indonesia, Order 033 Period 2012, which is 70 mg.kg.